Improving Student Mathematics Learning Outcomes Through the Implementation of the Talking Stick Learning Model Assisted by Card Media - Tunggali, Harfiah Jannah; Kadir, Kadir; Asma, Andi (Journal of Elementary Educational Research, 2023)
This research was conducted to improve the learning outcomes of class III students at MI Al-Khairaat Mogolaing by applying the talking stick learning model with the help of card media. The type of research applied was Classroom Action Research, with research subjects consisting of 26 class III student participants and the homeroom teacher as teacher. Research instruments include student and teacher activity observation sheets and learning outcomes tests. The research data was analyzed qualitatively and quantitatively. The research showed that teacher activity increased from the good category in Cycle I to very good in Cycle II. Student activity also increased from good to very good category in each Cycle. Student completeness increased from 46% in Cycle I to 93% in Cycle II. Thus, using the talking stick learning model with the help of card media effectively improves student learning outcomes in mathematics subjects.